Tradisi Mangupa dalam Perspektif Hadis tentang Doa dan Keberkahan di Kecamatan Hutabargot - Roisul Hamdi Lubis; Munandar (STAIN MAJENE, 2026)
The Mangupa tradition is a preserved cultural heritage of the Mandailing community, particularly in Hutabargot District, Mandailing Natal Regency. This tradition serves as a form of prayer, blessing, and request for divine grace for individuals entering or experiencing important phases of life such as marriage, birth, circumcision, or migration. This study discusses the implementation of the Mangupa tradition, the values of prayer and blessing contained within it, and its harmony with the Prophetic traditions (hadith) of the Prophet Muhammad ﷺ. The practice of Mangupa reflects a harmonious integration between customary values and Islamic teachings, in which Islamic prayers are recited alongside Mandailing traditional expressions rich in moral and spiritual meaning. Each symbol used—such as white rice, a rooster, and eggs—bears deep philosophical significance representing sincerity, responsibility, and family unity. The people of Hutabargot understand barakah (blessing) not only as material prosperity but also as peace, safety, and life harmony attained through prayer and social cohesion. Moreover, this tradition aligns with the teachings of the Prophet’s hadiths, which emphasize gratitude, communal prayer, and maintaining social ties. Thus, Mangupa is not merely a cultural ritual but also a form of living hadith—a living embodiment of Islamic values expressed through social and cultural practices. Through Mangupa, it becomes evident that Islam and local culture coexist harmoniously, reflecting the religious, social, and cultural character of the Mandailing community.